Clinically approved immunomodulators ameliorate behavioral changes in a mouse model of hereditary spastic paraplegia type 11 - Hörner, Michaela; Popp, Sandy; Branchu, Julien; Stevanin, Giovanni; Darios, Frédéric; Klebe, Stephan; Groh, Janos; Martini, Rudolf (Frontiers in Neuroscience, 2024)
We have previously demonstrated that neuroinflammation by the adaptive immune system acts as a robust and targetable disease amplifier in a mouse model of Spastic Paraplegia, type 11 (SPG11), a complicated form of Hereditary Spastic Paraplegia (HSP). While we identified an impact of neuroinflammation on distinct neuropathological changes and gait performance, neuropsychological features, typical and clinically highly relevant symptoms of complicated HSPs, were not addressed. Here we show that the corresponding SPG11 mouse model shows distinct behavioral abnormalities, particularly related to social behavior thus partially reflecting the neuropsychological changes in patients. We provide evidence that some behavioral abnormalities can be mitigated by genetic inactivation of the adaptive immune system. Translating this into a clinically applicable approach, we show that treatment with the established immunomodulators fingolimod or teriflunomide significantly attenuates distinct behavioral abnormalities, with the most striking effect on social behavior. This study links neuroinflammation to behavioral abnormalities in a mouse model of SPG11 and may thus pave the way for using immunomodulators as a treatment approach for SPG11 and possibly other complicated forms of HSP with neuropsychological involvement.